Blood Bilirubin Content in Neonatal Tetanus Patient with Hyperbilirubinemia during Treatment with Intravenous Diazepam - Taslim S. Soeetomenggolo (Indonesian Pediatric Society, 1992)
An evaluation on 128 neonatal tetanus patients with hyperbilirubinemia was done at the Department of Child Health, Dr. Cipto Mangunkusumo General Hospital, Jakarta. The patients were treated with high dosages of diazepam intravenously. This drug is potential to cause the increase of blood bilirubin, and in turn this latter condition is potential to cause kernicterus. Of the 128 patients there were 70 males and 58 females. The age of the patients were mostly (79.6 %) 4- 7 days. Fourteen of the 128 patients showed the increase of their blood bilirubin content during the second day of treatment, but after that it declined gradually during the next 3 days. The mortality of the 14 patients was 8 (57.1 %), so far no kernicterus was recorded among them. Among the 128 patients, 114 patients showed the decrease of their blood bilirubin content during the treatment. During 3 days the blood bilirubin content became less than 10 mg/dL. No kernicterus was recorded among those patients. It was concluded that intravenous diazepam is not dangerous in patients with mild and moderate hyperbilirubinemia, and no kernicterus was recorded during evaluation.